Anterior cruciate ligament injuries result in a larger functional deficit in fighting sport athletes: comparison of functional status among different sport types. Issue 3 (20th March 2018) - Hiyama, Kanehiro; Nakagawa, Yusuke; Ohara, Toshiyuki; Muneta, Takeshi; Watanabe, Toshifumi; Horie, Masafumi; Otabe, Koji; Katagiri, Hiroki; Katagiri, Kenta; Katakura, Mai; Hoshino, Takashi; Ueki, Hiroko; et al.
Abstract : Objectives: To compare the effects of anterior cruciate ligament (ACL) injuries and the preoperative period on functional status in different sports using preoperative patient data from the Multicenter Arthroscopic Knee Surgery (MAKS) study, a multicentre prospective cohort study of patients who underwent ACL reconstructions and meniscal surgeries conducted in 2013. Methods: Of the 1648 patients registered in the MAKS study cohort, 826 underwent unilateral primary ACL reconstruction. These patients were divided into three groups based on sports activity type: contact, fighting and non-contact. The patients were further divided into two subgroups according to preoperative period data: acute (≤3 months) and chronic (>3 months). We standardised the preoperative evaluation items (Knee injury and Osteoarthritis Outcome Score (KOOS), International Knee Documentation Committee (IKDC) subjective form, and Lysholm score) and surgical records. Results: The mean Lysholm score in the non-contact group was statistically significantly better than that in the fighting group. The two KOOS subcategories were statistically significantly superior in the non-contact group than in the fighting group. In the contact group, acute cases showed statistically significantly lower IKDC subjective scores and lower scores in two KOOS subcategories than the chronic cases. In the fighting group, chronic cases showed better IKDC subjective scores and scores for three KOOS subcategories than the acute cases. In the non-contact group, chronic cases showed better IKDC subjective scores and scores for all KOOS subcategories than the acute cases. Conclusion: When athletes with ACL injuries are divided by sport type into fighting, contact and non-contact groups, the functional status of fighting sport athletes was more negatively influenced by ACL injury than those of non-contact sport athletes. When divided into acute and chronic phases, overall acute cases showed lower scores than the chronic cases in all sport types. In acute cases, the functional status of fighting sport athletes was more negatively influenced than non-contact sport athletes, whereas in chronic cases, there were no differences among the different sport types. The sport types and postinjury period should be considered for decision-making on therapeutic measures of patients with ACL injuries. Level of evidence: Level II.